Modern Neonatal Transport: Sound and Vibration Levels and Their Impact on Physiological Stability - Bailey, Vickie; Szyld, Edgardo; Cagle, Kristi; Kurtz, Deborah; Chaaban, Hala; Wu, Dee; Williams, Patricia (American Journal of Perinatology, 2019)
Objective To measure sound and vibration in rotary wing air transport (RWAT) and ground ambulance transport (GAT), comparing them to current recommendations, and correlating them with physiological stability measures in transported neonates.Study Design This is a prospective cohort observational study including infants ≤ 7 days of age transported over an 8-month period. Infants with neurologic conditions were excluded. Sound and vibration was continuously measured during transport. Transport Risk Index of Physiologic Stability (TRIPS) scores were calculated from vital signs as a proxy for physiological stability.Results In total, 118 newborns were enrolled, of whom 109 were analyzed: 67 in RWAT and 42 in GAT. Peak sound levels ranged from 80.4 to 86.4 dBA in RWAT and from 70.3 to 71.6 dBA in GAT. Whole-body vibration ranged from 1.68 to 5.09 m/s2 in RWAT and from 1.82 to 3.96 m/s2 in GAT. Interval TRIPS scores for each infant were not significantly different despite excessive sound and vibration.Conclusion Noise levels during neonatal transport exceed published recommendations for both RWAT and GAT and are higher in RWAT. Transported infants are exposed to vibration levels exceeding acceptable adult standards. Despite excessive noise and vibration, levels of physiological stability remained stable after transport in both RWAT and GAT groups.
Keywords: newborn; transport; sound; vibration